2013
DOI: 10.1111/ter.12019
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Variscan exhumation of the Central Anti‐Atlas (Morocco) constrained by zircon and apatite fission‐track thermochronology

Abstract: The origin of the Anti‐Atlas relief is one of the currently debated issues of Moroccan geology. To constrain the post‐Variscan evolution of the Central Anti‐Atlas, we collected nine samples from the Precambrian basement of the Bou Azzer‐El Graara inlier for zircon and apatite fission‐track thermochronology. Zircon ages cluster between 340 ± 20 and 306 ± 20 Ma, whereas apatite ages range from 171 ± 7 Ma to 133 ± 5 Ma. Zircon ages reflect the thermal effect of the Variscan orogeny (tectonic thickening of the ca.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 43 publications
8
51
0
Order By: Relevance
“…However, it is in agreement with recent studies that have revealed the existence of major tectonic vertical motions that affected large domains on the eastern margin of the Central Atlantic Ocean (Malusà et al 2007;Ghorbal et al 2008;Ghorbal 2009;Gouiza 2011;Ruiz et al 2011;Bertotti and Gouiza 2012;Oukassou et al 2013;Sehrt 2014;Leprêtre et al 2015). Thereby, our data and the subsequent interpretation imply that the Anti-Atlas domain experienced up to 10.5 km of crustal exhumation and denudation by the Middle Jurassic, in relation with continental rifting in the Central Atlantic and the Tethyan Atlas.…”
Section: Oligocenesupporting
confidence: 93%
See 3 more Smart Citations
“…However, it is in agreement with recent studies that have revealed the existence of major tectonic vertical motions that affected large domains on the eastern margin of the Central Atlantic Ocean (Malusà et al 2007;Ghorbal et al 2008;Ghorbal 2009;Gouiza 2011;Ruiz et al 2011;Bertotti and Gouiza 2012;Oukassou et al 2013;Sehrt 2014;Leprêtre et al 2015). Thereby, our data and the subsequent interpretation imply that the Anti-Atlas domain experienced up to 10.5 km of crustal exhumation and denudation by the Middle Jurassic, in relation with continental rifting in the Central Atlantic and the Tethyan Atlas.…”
Section: Oligocenesupporting
confidence: 93%
“…This is in agreement with ZFT ages obtained on samples from the western and central Anti-Atlas, which indicate that the currently exposed basement rocks were at temperatures around 300-240 °C between 350 and 280 Ma (Fig. 7) (Sebti et al 2009;Oukassou et al 2013;Sehrt 2014).…”
Section: Paleozoic Evolutionsupporting
confidence: 90%
See 2 more Smart Citations
“…Oligocene deposits are not observed in this region of Morocco. Southward, Paleozoic and Precambrian formations outcrop in the Anti-Atlas, due to the erosion of a previous thin Mesozoic-Cenozoic cover (Ruiz et al, 2011;Oukassou et al, 2013). Two main fault system strikes can be distinguished in the Imini area: a N45° to N90° striking group and a N110°-N130° striking group in the area (Fig.…”
Section: Imini Districtmentioning
confidence: 95%